Use of ontological knowledge by intelligent agents - Rogushina, J.V. (Інститут програмних систем НАН України, 2018)
Ontological means of knowledge representation in the Web-oriented intelligent information systems are considered. The formal model of ontology that ensures the use of knowledge from various distributed applications that support semantic information processing is proposed. The specifics of this model is a separation into the special group of characteristics of such ontological elements as classes and object and data properties – hierarchical, disjoint and equivalent etc. Use of ontologies into the intelligent applications differs significantly according with their role – internal and external. The properties of internal and external ontologies and their use by intelligent personal software agents whose behavior is modeled through the apparatus of intentional relations (beliefs, knowledge and purpose) are considered. Personal  software agents are considered as a subclass of computer agents. Their intelligence level is analyzed as far as their management of distributed knowledge  is concerned. Problems in programming 2017; 2: 82-95